Synagogen in Göttingen : Aufbrüche und Abbrüche jüdischen Lebens - Schaller, Berndt 1930-2020 (Univ.-Verl. Göttingen, 2006)
The book "Synagogues in Göttingen: departures and ceasing of Jewish life," deals with the 700-year history of Jewish life in Göttingen and the various synagogues that have been existing since the beginning of the 14th Century